Análisis de textura en frutas - Esquivel Reyes, Nancy Verónica (2017)
Nowadays, the selection of food is based more and more on the quality of the product, which is a very complex concept in which different aspects intervene, such as the acceptance of consumers and the opinion of experts, that is why that it is important to determine the quality of the food in a physical-chemical and sensorial environment. An important point when accepting or rejecting a food is its texture, since this is a mixture of the elements related to its structure and the way they relate to the physiological senses. At present, several studies have been carried out aimed at detailing the main textural characteristics of different fruits. The analysis of the texture profile, is an excellent instrumental procedure, that simulates the mastication of the jaw; helps to measure and quantify parameters such as: hardness, gumminess, chewiness, elasticity, cohesiveness among others, which are related in turn to variables such as the rate of applied deformation and the composition of the product, on the other hand the sensory parameters, physicochemical tests and the instrumental analyzes can be used as quality standards, since together they can better characterize products for human consumption, increasing the acceptability by consumers to these foods. The results indicate that the final perception of the texture is based on the human sensory evaluation, while the instrumental perception on destructive and non-destructive methods. However, there is still a lack of international standards for fruit texture measurement, which often makes it difficult to track and compare the results of the research, even on the same product and using the same instrument; In the present work a revision is carried out, on the current state, the methods of texture determination in fruits; sensory, instrumental and physicochemically of different fruits to obtain new results that guarantee its quality, including its properties, characteristics, and the importance it has in the food industry.